EFFECTIVENESS OF SUPERVISED FITNESS AND MOBILITY EXERCISE PROGRAM ON FITNESS, MOBILITY AND MUSCLE STRENGTH IN YOUNG ADULTS WITH STROKE (International Journal of Physiotherapy, 2014)
Background: Stroke is a major disabling health problem in developing countries like India & causes long term disability. Long term disability furthers leads to global burden and other psychological problems.The FAME i.e., fitness and mobility exercise program has been designed to improve mobility, fitness and muscle strength. This protocol is community based protocol and helps in patients independent lifestyle.Objective is to examine the effect of supervised FAME protocol on fitness with 6minutes walk test, on mobility with timed up go test & on hamstrings muscle strength measured as hamstrings peak torque with isokinetic analyzer.Methods: Stroke participants were recruited into the study as per the inclusion and exclusion criteria and randomized into intervention group (n = 15) and control group (n = 15).The intervention group underwent supervised fitness and mobility exercise program & the control group underwent home exercises with printed FAME material (telugu & English version).This program was designed for 8 weeks (3 sessions / week). 6MWT- used to evaluate cardio respiratory fitness, TUG test- used to evaluate mobility, Isokinetic analyzer- used to evaluate hamstrings peak torque. Base line measurements are taken prior to the intervention and post intervention values taken after the 8 weeks of intervention.Results: Variables within the groups were compared by using paired t test and between the groups by using independent t test. According to obtained values, the pre & posttest values of 6MWT, TUG test & hamstrings peak toque had a significant effect on p-values